Anti-Hepatocellular Carcinoma Effect and Molecular Mechanism of the Estrogen Signaling Pathway - Guo, Yusheng; Wu, Guohui; Yi, Junrong; Yang, Qin; Jiang, Wengong; Lin, Shaoqiang; Yang, Xiaorong; Cai, Xiangsheng; Mao, Liufeng (Frontiers in Oncology, 2022)
There are significant gender differences in the incidence and mortality of hepatocellular carcinoma (HCC). Compared with men, the incidence and mortality of HCC in women are relatively low. The estrogen signaling pathway, composed of estrogen and estrogen receptors, has been postulated to have a protective effect on the occurrence and development of HCC. There have been multiple studies that have supported anti-HCC effects of the estrogen signaling pathways, including direct and indirect pathways such as genomic pathways, rapid transduction pathways, non-coding RNA, tumor microenvironment, estrogen metabolites, and inhibition of hepatitis infection and replication. Based on the evidence of an anti-HCC effect of the estrogen signaling pathway, a number of strategies have been investigated to determine the potential therapeutic effect. These have included estrogen replacement therapy, targeting the estrogen receptor, key molecules, inflammatory mediators, and regulatory pathways of the estrogen signaling pathway. In this review, we have systematically summarized the latest developments in the complex functions and molecular mechanisms of the estrogen signaling pathway in liver cancer. Furthermore, we have highlighted the potential targets of treatment strategies based on the estrogen signaling pathway in the treatment of liver cancer and the principal obstacles currently encountered for future investigation.